Mutant allele specific imbalance in oncogenes with copy number alterations: Occurrence, mechanisms, and potential clinical implications. (1st January 2017) - Yu, Chih-Chieh; Qiu, Wanglong; Juang, Caroline S.; Mansukhani, Mahesh M.; Halmos, Balazs; Su, Gloria H.
Abstract: Mutant allele specific imbalance (MASI) was initially coined to describe copy number alterations associated with the mutant allele of an oncogene. The copy number gain (CNG) specific to the mutant allele can be readily observed in electropherograms. With the development of genome-wide analyses at base-pair resolution with copy number counts, we can now further differentiate MASI into those with CNG, with copy neutral alteration (also termed acquired uniparental disomy; UPD), or with loss of heterozygosity (LOH) due to the loss of the wild-type (WT) allele. Here we summarize the occurrence of MASI with CNG, aUPD, or MASI with LOH in some major oncogenes (such as EGFR, KRAS, PIK3CA, and BRAF ). We also discuss how these various classifications of MASI have been demonstrated to impact tumorigenesis, progression, metastasis, prognosis, and potentially therapeutic responses in cancer, notably in lung, colorectal, and pancreatic cancers. Highlights: This review describes and explains various classes of MASI pertaining to oncogenes and their significance in tumorigenesis. MASI at the EGFR and KRAS loci and their impacts on tumorigenesis and profound clinical implications are highlighted. The putative tumor-suppressive role of the wild-type KRAS allele in the context of the oncogenic KRAS allele is discussed.